(untitled) - Chubb, Bruce A. (Massachusetts, 1967)
This book presents a first concerted effort to combine, using a digital computer, statistical tolerance techniques and servo design. It provides a simple, straightforward , and realistic method of considering all tolerance effects.
Keywords: Servomechanisms,Cơ phục vụ